2019
DOI: 10.4314/ijbcs.v13i1.37
|View full text |Cite
|
Sign up to set email alerts
|

Investigations ethnobotaniques de <i>Momordica charantia</i> Linn (Cucurbitaceae) au Sénégal

Abstract: La nécessité d'habilitation des plantes utilisées en médecine traditionnelle africaine a suscité des investigations sur Momordica charantia Linn (Cucurbitaceae) dont les connaissances sont empiriques. L'étude ethnobotanique a été menée dans quatre (4) régions du Sénégal pendant la campagne 2016/2017, dans le but de préciser ses différents usages en pratiques médicales et voire alimentaires. Lesrésultats montrent que les feuilles et la tige sont utilisées chacune dans 91,50% des cas. Elles sont utilisées essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
1
9
0
1
Order By: Relevance
“…The potassium content of seeds of M. charantia is respectively 936.38; 882.82 and 893.67 mg•100 g −1 , while that of calcium is 721.21; 837.05 and 803.76 mg•100 g −1 . These results are consistent with those found in the fruit pulp in which potassium and calcium are the dominant minerals [22]. Therefore the seeds are richer in mineral elements than the fruit pulp.…”
Section: Study Of Geographic Variability and Mineral Elements Of Seedssupporting
confidence: 91%
See 1 more Smart Citation
“…The potassium content of seeds of M. charantia is respectively 936.38; 882.82 and 893.67 mg•100 g −1 , while that of calcium is 721.21; 837.05 and 803.76 mg•100 g −1 . These results are consistent with those found in the fruit pulp in which potassium and calcium are the dominant minerals [22]. Therefore the seeds are richer in mineral elements than the fruit pulp.…”
Section: Study Of Geographic Variability and Mineral Elements Of Seedssupporting
confidence: 91%
“…Indeed, some studies have highlighted the morphological, phenological and biochemical differences between populations of M. charantia. This study also revealed variability in seed shell mass (0.113 ± 0.023 and 0.098 ± 0.051 g) [22]. The difference in size between seeds from Senegal (Dakar and Fatick) and those from Togo is probably the result of pedoclimatic conditions and genetic variability.…”
Section: Study Of Geographic Variability and Mineral Elements Of Seedsmentioning
confidence: 51%
“…The specie belonging to the Cucurbitaceae family, is commonly called gourd or "bitter gourd", linked to bitter compounds contained in all parts of the plant including the fruit [1]. Momordica charantia is widely cultivated in the tropical Food and Nutrition Sciences and subtropical regions of the world, such as India, Malaysia, China, Thailand, Japan, and Senegal [2] [3] [4]. The fruit of M. charantia is oblong or base with buds and resembles a small cucumber that has been used for nutritional and medicinal purposes [1] [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed the socio-economic value of these resources such as those from Adansonia digitata, Irvingia gabonensis / Irvingia wombolu, Dacryodes edulis, Ricinodendron heudelotii, Garcinia kola, Chrysophyllum albidum, Cola spp etc. to the national economy and livelihoods in West Africa (Timko et al, 2010;Heubes et al, 2012) ; Neumann and Hirsch, 2000;Belcher and Vantomme, 2003;Bayeli et al, 2019;Balde et al, 2019). They are particularly important for ensuring food security and maintaining nutritional balance in the diet of populations.…”
Section: Introductionmentioning
confidence: 99%